Occupational Allergic Contact Dermatitis in Healthcare Workers - Pinheiro, Vítor (2017)
Introduction: Occupational allergic contact dermatitis (ACD) is frequent among health care workers (HCW) and culprit allergens may vary with time, occupational setting and exposure hazards.Objectives and Methods: In order to characterize the main contact allergens in HCW with dermatitis and its occupational relevance, we performed a retrospective analysis of clinical data and patch test (PT) results from HCW who were studied in the Department of Dermatology of Coimbra Hospital and University Centre (CHUC) between 2010-2015. All patients were tested with a baseline and additional series, according to the tasks developed.Results: Among 1858 patch tested patients, 125 (6.7%) were HCW, 114 females/11 males, mean age 39,26±12,5 years, mainly nurses (56), technical assistants (48) and doctors (21), 71 with hand dermatitis (56,8%), 22 with atopic dermatitis and/or other atopic symptoms (17,6%). Ninety patients (72%) had at least one positive PT, 47 (37,6%) with occupational relevance. Patients with hand dermatitis were significantly more likely to have positive PT (76.1%). We observed 51 positive PT to metals (Ni-41, most with past relevance, Co-8; Cr -2), 30 to fragrances (FM-I-10; Myroxylon pereirae-8; lyral-5; FM-II-4; citronellol-3), 29 to preservatives (mostly methylisothiazolinone (MI) and/or chloromethylisothiazolinone (MCI)-20), 24 to rubber chemicals (P-phenylenediamine (PPD)/Isopropyl-PPD-9), and 14 to topical medicaments (iodopovidone - 5; caine mix - 4). The main occupational causes of ACD were hand soaps/disinfectants and patients’ hygiene products (15), protective gloves/shoes-9 and topical or systemic drugs (antiseptics-8 and parenteral antibiotics-3). Main allergens with occupational relevance were MI and/or MCI/MI (15), although isolated MI was tested only after mid 2012, lanolin and/or amerchol L101 (9), formaldehyde and/or formaldehyde releasers (7), iodopovidone (5), thiuram mix (5), carbamates (4), FM-I (3), cephalosporins (3) and (meth)acrylates (3 dentists/dental technicians). In 37 out of 42 evaluated cases there was marked improvement/resolution of the dermatitis, namely after eviction of the hospital hand soap which contains MCI/ MI under the designation of Acticide® MV.Conclusions: Hand dermatitis was the main presentation of ACD in HCW with no apparent relation with atopy. Isothiazolinones and formaldehyde releasers induced more positive PT and were more frequent among HCW than in the whole population studied very probably due to the cumulative exposure to these preservatives in personal and occupational hand soaps and hygiene products. PT was important to orient eviction in each individual case but also for the hospital community to understand the presence of moderate or potent sensitizers in the work place and, therefore, establish the most adequate preventive measures.